Pengaruh Model Pembelajaran Time Toke Terhadap Kemampuan Menulis Teks Prosedur Siswa Kelas XI SMA Negeri 19 Palembang - Febrianti, Febrianti; Misriani, Misriani; Effensi, Darwin (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine the effect of the time token learning model on the ability to write procedural texts for class XI students of SMA Negeri 19 Palembang. The research method used is the Poss Experiment - test Only Control Design method. test data collection. The data analysis technique used is a test technique. The results of the study on the ability to write procedural texts for class XI students of SMA Negeri 19 Palembang. The results of the calculation of student learning data valuesusing the t-test (T Test from Anova) contained in a SPSS V 22 program show that which means if the Sig value > 0.05, then the data distribution is homogeneous, and if the Sig value < 0.05 then the data distribution not homogeneous. The result of the calculation of the significant value above the value obtained is a t-test of 0.28 > 0.5. It means that the Sig value > 0.05, the researcher concludes that "There is an influence of the Time Token Learning Model on the Ability to Write Procedure Texts for Class XI Students of SMA Negeri 19 Palembang".